Junction of the redox dynamic, orchestra of signaling, and altered metabolism in regulation of T- cell lymphoma - Singh, Shantanu; Maurya, Akhilendra Kumar (Frontiers in Oncology, 2023)
T cell lymphoma is a hematologic neoplasm derived from lymphoid linage mostly affecting young population worldwide. It is a diverse group of malignant disorder that varies with respect to the molecular feature as well as genetic and clinical approaches. Gaining insight into cancer metabolism is brightening the importance of nutrient supply to tumor development and therapeutic responses. A precision approach required a detailed understanding of the molecular mechanisms that determine the metabolic vulnerabilities of lymphoma. Cancer cells rewire cellular metabolism to satisfy the demands of growth and proliferation. Metabolic alterations and heterogeneity are largely similar to those in normal proliferating cells; they are aberrantly driven in cancer by a combination of genetic lesions and non-genetic factors such as the tumor microenvironment. Together these altered tumor metabolism is regarded hallmark of cancer. Imbalance in redox state of oxidative species results in oxidative stress caused due to exogenous and/or endogenous factors which is closely related to all aspect of the cancer from carcinogenesis to the tumor bearing state, from treatment to prevention. Different oncogenic signalling molecules including tumor suppresser, inflammatory mediators etc, are regulated through different redox sensor such as nuclear factor E2-related factor 2(Nrf2), phase-II antioxidant enzyme and NQO1 (NADPH quinone oxidoreductase 1). Oxidative state deflected from its redox threshold result in alteration of signalling pathway and governs multiple intracellular signal transduction and transcription factors which lead to carcinogenesis and tumor progression. Therefore, there is need of concrete codify framework based on molecular pattering of T-cell lymphoma regulated by oxidants. Current review highlighted on the redox dynamics, orchestrated signaling and genetic regulation in T- cell lymphoma progression, in conjugation with insight in their molecular mechanism and challenges in their etiology, treatment and their clinical relevance in light of recent updates.